Research of Automated Control Systems Development Based on “Publish-Subscribe” Technology Over Low-Bandwidth Radio Networks - Стрелковська, Ірина Вікторівна; Стрелковська, І. В.; Стрелковская, Ирина Викторовна; Strelkovska, Iryna V.; Zolotukhin, Roman V.; Золотухін, Роман (Springer International Publishing, 2021)
The development of automated control systems (ACS) based on low- bandwidth communication networks ofUHF/VHF radio stations is themajor problem concerning the system nodes intercommunication and information exchange. The high-throughput communication networks have solved this problem by means of algorithms and protocols based on “publish-subscribe” technology. However, it is necessary to research the ability to use such technology over low-bandwidth commu- nication networks. This research is focused on automated control systems develop- ment based on Message Queuing Telemetry Transport (MQTT) and Data Distribu- tion Service (DDS) by Object Management Group (OMG) protocols. The ability to use such mechanism of data exchange over governmental ACS of the low echelon management level based on VHF/UHF radio stations with high requirements to safety, liveliness and reliability are shown. The MQTT, MQTT-SN and DDS proto- cols analysis was performed. The data about service packets quantity, lost packets quantity, maximal packet size, actual volume of service and information data was performed and the time of communication establishment betweenMQTT,MQTT-SN and DDS nodes was deﬁned. The recommendations concerning “publish-subscribe” protocols usage in ACS development were given.
Strelkovska I. V. Research of Automated Control Systems Development Based on “Publish-Subscribe” Technology Over Low-Bandwidth Radio Networks / I. V. Strelkovska, R. V. Zolotukhin // Lecture Notes in Networks and Systems (LNNS,vol.548). - 2021. - P. 257-275.
Keywords: Publish-subscribe; MQTT; MQTT-SN; DDS; ACS; QoS; Trafﬁc characteristics; UHF/VHF radio station; Low-bandwidth network; Broker; Gateway; RTPS; Research Subject Categories::TECHNOLOGY